A design rationale to support data use in successful teacher practice: some considerations for educational technology design. Issue 1 (20th March 2020) - Wardrip, Peter Samuelson; Herman, Phillip
Despite the growing ubiquity of educational technologies in K-12 classrooms, many scholars have pointed out that impact of these technologies for all students has been uneven (Gomez et al., 2010). Some attribute this to a lack of cumulativity in educational research, in general. In this paper, we present design rationale as a mechanism to support designers building upon others' designs and assumptions of designs. Reporting on design-based research study to support teachers' data-informed instruction, we highlight our own process connecting our decisions and outcomes to both the conditions on the ground as well as the current research literature.